Emotional Abuse in Intimate Relationships: A Qualitative Study among married people - Anusree., K.B; Kajal., U.K; Sindhu., D.M; Rajkumar, Eslavath; Lakshmi, R.; Romate, J.; Abraham, John; Joshua George, Allen; L, Rajashekaran (International Journal of Psychosocial Rehabilitation, 2021)
Context: Intimacy being a crucial part of marriage is often misunderstood that only couple with less intimacy experience emotional abuse. But whether highly intimate married couple also experience emotional abuse is not clearly understood. So the present study emphasized on exploring the emotional abuse among highly intimate married couples.  Aim: To explore emotional abuse in intimate relationships among married people.Method: The data was collected from 10 participants using in-depth interviews, living inIndia, who are in an intimate (married) relationship. The data was analysed using qualitative thematic analysis.Results: After analysing the qualitative content of the interviews, the following five themes were emerged: Verbal abuse, emotional insecurities, degradation, lack of affiliation, and negative view on life. Conclusions: Even highly intimate married couples experience emotional abuse. The findings have important applications in developing healthy relationship among married couples.